2005
DOI: 10.1002/pssa.200420062
|View full text |Cite
|
Sign up to set email alerts
|

Hall effect of copper nitride thin films

Abstract: The Hall effect of copper nitride (Cu 3 N) thin films was investigated in our work. Cu 3 N films were deposited on glass substrates by radio-frequency (RF) magnetron sputtering at different temperatures using pure copper as the sputtering target. The Hall coefficients of the films are demonstrated to be dependent on the deposition gas flow rate and the measuring temperature. Both the Hall coefficient and resistance of the Cu 3 N films increase with the nitrogen gas flow rate at room temperature, while the Hall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2007
2007
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
1
5
1
Order By: Relevance
“…It is worthwhile to mention here that our results contrast somehow with those reported by Yue et al [12,40] using Hall measurements, suggesting that the Cu 3 N shows an n-type semiconductor behaviour. In our opinion the divergences found in the behaviour of the material should be explained in terms of difference in film stoichiometry.…”
Section: Discussioncontrasting
confidence: 87%
“…It is worthwhile to mention here that our results contrast somehow with those reported by Yue et al [12,40] using Hall measurements, suggesting that the Cu 3 N shows an n-type semiconductor behaviour. In our opinion the divergences found in the behaviour of the material should be explained in terms of difference in film stoichiometry.…”
Section: Discussioncontrasting
confidence: 87%
“…All samples exhibit a negative S coefficient which decreases from -5 uV/K to -50 uV/K with rising nitrogen concentration from 26 ± 2 to 33 ± 2 at.%. The negative sign of S indicates that the majority of the carriers must be electrons, being consistent with previously reported Hall effect data [23,28], The relatively small S value for the stoichiometric film might indicate that electron and hole carrier densities are almost compensated, as expected for an intrinsic semiconductor. For N-rich samples the absolute value of S, \S\, remarkably increases with rising nitrogen content, being up to one order of magnitude higher for the sample containing 33 at.% of nitrogen than for the stoichiometric one.…”
Section: Resultssupporting
confidence: 90%
“…Experimental data [27] have revealed that for films sputtered under the same conditions, extra nitrogen (or at least a high fraction of it) incorporates in the film in interstitial positions forming a solid solution and expanding the crystal lattice in comparison to stoichiometric Cu 3 N. Moreover, spectroscopic ellipsometry and infrared absorption measurements carried out on N-rich Cu 3 N films have clearly indicated the presence of a free-carrier contribution in the optical spectra that has been related to the N excess [26]. The origin and nature of those extra carriers could not be elucidated in that work, partly due to the difficulty of carrying out reliable Hall measurements and the dispersion of so far reported data [23,28], In order to clarify the experimental situation and to assess the electronic role of the excess N in Cu 3 N experiments: electrical conductivity, spectroscopic ellipsometry at several temperatures and [23,28], that have not, so far, provided conclusive results. In fact, it has been claimed that Seebeck coefficient measurements often offer better reproducibility [29] than Hall Effect experiments.…”
Section: Introductionmentioning
confidence: 94%
“…The achieved electrical resistivity of the films formed at the sputtering power of 75 Watts was in good agreement with the rf magnetron sputtered films. [9] The dependence of optical transmittance on the wavelength of the Cu 3 N films formed at different sputtering powers is shown in Figure 4. The optical transmittance of the films (wavelength .…”
Section: Resultsmentioning
confidence: 99%